Enhancing Community Preparedness for Disasters through the Safe School Program (SPAB) in Cilacap Regency - Mudzrikatun Chabibah; Nurul Ngatiqoh; W. Warto (Empower : Jurnal Pengembangan Masyarakat Islam, 2025)
This article discusses the SPAB program in increasing community preparedness in facing disasters that can occur anytime and anywhere. This research uses a qualitative descriptive method, which uses articles, journals and books as well as interviews with parties related to this research theme to obtain detailed information. The objectives of this research are 1) to determine the implementation of the Disaster Safe Unit Program (SPAB) in Cilacap Regency; 2) knowing the obstacles in implementing the disaster safe education unit program; 3) stages in implementing the disaster safe education unit program. The implementation of the disaster safe education unit program in Cilacap district has not been carried out optimally due to several obstacles that have occurred, one of which is a lack of budget, resulting in inadequate assets. There is a need to improve strategies in implementing the Disaster Safe Education Unit program so that it can run effectively and in accordance with the stated objectives